Pengaruh Foto Produk dan Customer Rating terhadap Keputusan Pembelian melalui Aplikasi GoFood - Sipa Paujiah; Aripin Ahmad; Mutiasari Nur Wulan (Reviu Akuntansi, Manajemen, dan Bisnis, 2022)
Purpose: The purpose of this study was to determine purchasing decisions on the GoFood application as measured by two aspects, namely product photos and customer ratings. This research can help food and beverage sellers, especially restaurants, as GoFood partners, display attractive product photos to influence consumers' purchasing decisions. Research methodology: This research is quantitative research with a survey method through an online questionnaire. The sampling technique used was purposive sampling, where the respondents were consumers who had bought food and beverages on the GoFood application, as many as 101 respondents. The analysis technique in this study is an analysis of the characteristics of the respondents; validity and reliability test; classical assumption test; correlation coefficient test (r); coefficient of determination test (R2); F test; and t test. Results: The results of the study simultaneously show that the product photo (X1) and customer rating (X2) variables simultaneously affect purchasing decisions through the GoFood application. The product photo (X1) and customer rating (X2) variables on purchasing decisions indicate that the better the product photos displayed, the greater the purchasing decisions made by consumers on the GoFood application. Limitations: Researchers only focus on the GoFood application, while there are still many other food and beverage service provider applications and the number of respondents is still very low to describe the actual situation. Contribution: enriching knowledge in the field of digital marketing, specifically about the effect of product photos and customer ratings on purchasing decisions.